Web design all-in-one for dummies - Jenkins, Sue, 1966- (Hoboken, N.J. : Wiley, 2013)
Web design includes so many tasks, but here's the information you need to complete each one! Learn to develop goals for your site, target your audience, design a layout, mock up your design, and optimize the graphics. Then grab your techie hat and learn to build your site with HTML and CSS.
-- Introduction -- Getting started -- Designing for the Web -- Building websites -- Web standards and testing -- Publishing and site maintenance.
Includes index.
Keywords: Web sites -- Design